Epstein-Barr virus-associated hemophagocytic lymphohistiocytosis in a postpartum patient with preeclampsia: a case report - Bruce Lee, MD; Peter Kouides, MD; Stephanie Bousquet, MD; Paul Cabral, MD (Elsevier, 2021)
Hemophagocytic lymphohystiocytosis is an extremely life-threatening immune deregulatory syndrome. It is characterized by pathologic activation of immune cells, leading to excessive cytokine production, multiorgan failure, and potentially, death. A 28-year-old primigravida at 32 weeks and 3 days of gestation presented with newly-diagnosed preeclampsia with severe features, fever, and fetal tachycardia. She was delivered by cesarean delivery. After delivery, she had a fever of unknown origin, with evidence of a hyperinflammatory state. Extensive infectious work-up was significant for positive Epstein-Barr Virus. A bone marrow biopsy demonstrated hemophagocytosis. She was diagnosed with Epstein-Barr-Virus-associated hemophagocytic lymphohystiocytosis and was treated with immunosuppression and chemotherapy. Hemophagocytic lymphohistiocytosis is a rare, life-threatening immune dysregulatory syndrome with both genetic and extragenic triggers that can occur in the postpartum period. Rituximab is an effective add-on therapy to conventional treatment.